2021
DOI: 10.3390/ijms22105068
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria Single-Cell and Photosensitizer Interaction Revealed by Quantitative Phase Imaging

Abstract: Quantifying changes in bacteria cells in the presence of antibacterial treatment is one of the main challenges facing contemporary medicine; it is a challenge that is relevant for tackling issues pertaining to bacterial biofilm formation that substantially decreases susceptibility to biocidal agents. Three-dimensional label-free imaging and quantitative analysis of bacteria–photosensitizer interactions, crucial for antimicrobial photodynamic therapy, is still limited due to the use of conventional imaging tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 68 publications
(80 reference statements)
1
11
0
Order By: Relevance
“…Therefore, it can be seen that in the case of all samples and bacteria species, similar averaged RI values of single cells represented at least from 65% to 90% of all the observations, which confirms the lack of differences between the samples and that the PS was not penetrating the cells. However, it should be noted that the increase in the average RI of single cells that were related to the increase in cell density can be associated not only with the accumulation of PS in the cell interior or cell membranes, but also with physiological processes such as cell division, which was confirmed by our previous results [ 23 ].…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Therefore, it can be seen that in the case of all samples and bacteria species, similar averaged RI values of single cells represented at least from 65% to 90% of all the observations, which confirms the lack of differences between the samples and that the PS was not penetrating the cells. However, it should be noted that the increase in the average RI of single cells that were related to the increase in cell density can be associated not only with the accumulation of PS in the cell interior or cell membranes, but also with physiological processes such as cell division, which was confirmed by our previous results [ 23 ].…”
Section: Resultssupporting
confidence: 85%
“…If the PS was released from the silica surface, it would penetrate the bacterial cells, which could be tracked by the presence of the luminescence signal inside the cell. These results were also confirmed by digital holographic tomography (DHT) [ 21 , 22 ] a label-free quantitative phase imaging technique, as our previous studies confirmed that the penetration of single bacteria cells by PS is related to the increase in the average refractive index (RI) of the cell [ 23 ]. The performed examinations confirmed that, in case of the lack of PS accumulation inside the bacteria cells, their death is caused directly by the generated free radicals.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…In our approach, the increase in the average RI value of bacteria cells was related to the increase in cell density caused by the accumulation of PS. The accumulation of PS in the cell interior or cell membranes leads to an increase in RI value but can also be associated with physiological processes such as cell division [ 26 ]. To obtain a representative set of data for this analysis, 20 tomograms (3D-RI) of each group were examined.…”
Section: Resultsmentioning
confidence: 99%
“…The accumulation of PSs was investigated by digital holotomography (DHT) using the refractive index (RI) as an imaging contrast for 3D label-free live bacteria cell imaging, since RI is related to the optical density of cells related to their mass and the cellular concentration of individual components [ 25 ]. As confirmed, the accumulation of photosensitizers within bacteria cells leads to changes in cell density and, consequently, to changes in RI values [ 25 , 26 ]. In a recent study, it was demonstrated that DHT is able to indicate, in a quantitative, nondestructive, and label-free manner, the difference in PS accumulation inside the bacteria cells with the use of each PS individually and in combination.…”
Section: Introductionmentioning
confidence: 96%